A female with X-linked Alport syndrome and compound heterozygous COL4A5 mutations - Mohammad, Mardhiah; Nanra, Ranjit; Colville, Deb; Trevillian, Paul; Wang, Yanyan; Storey, Helen; Flinter, Frances; Savige, Judy (Springer Berlin Heidelberg, 2014)
Background Female subjects with X-linked Alport syndrome have a single COL4A5 mutation, germ cell mosaicism in affected tissues and typically develop renal failure later or less often than male subjects. Women with two mutations are exceedingly rare, and usually have consanguineous parents or uniparental disomy. We describe here a 20-year-old woman who inherited two different COL4A5 variants, one from her father (c.2677G>C) and one from her mother (c.384 +1 G>A).